2018
DOI: 10.1038/s41467-018-03211-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of friction on oxidative graphite intercalation and high-quality graphene formation

Abstract: Oxidative wet-chemical delamination of graphene from graphite is expected to become a scalable production method. However, the formation process of the intermediate stage-1 graphite sulfate by sulfuric acid intercalation and its subsequent oxidation are poorly understood and lattice defect formation must be avoided. Here, we demonstrate film formation of micrometer-sized graphene flakes with lattice defects down to 0.02% and visualize the carbon lattice by transmission electron microscopy at atomic resolution.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 48 publications
0
76
0
3
Order By: Relevance
“…Consequently, the degree of oxidation is very similar for oxo‐G ref and oxo‐G B . In contrast, for oxo‐G 4 % the degree of functionalization is only about 4 %, and consequently a C content of about 86 % is found.…”
Section: Figurementioning
confidence: 86%
See 2 more Smart Citations
“…Consequently, the degree of oxidation is very similar for oxo‐G ref and oxo‐G B . In contrast, for oxo‐G 4 % the degree of functionalization is only about 4 %, and consequently a C content of about 86 % is found.…”
Section: Figurementioning
confidence: 86%
“…Upon washing the ionic strength is reduced, which triggers delamination of this oxo‐G by osmotic swelling. In addition, oxo‐G 4 % was synthesized from the intercalation compound graphite sulfate and aqueous treatment . Oxo‐G 4 % possesses, to a first approximation, 4 % of hydroxyl addends related to the number of C atoms .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In früheren Studien haben wir die Art der Gitterdefekte von oxo‐ S G/ S G und oxo‐ * G/ * G mittels Transmissionselektronenspektroskopie mit atomarer Auflösung visualisiert. Es handelt sich um Defekte mit wenigen fehlenden C‐Atomen (Fehlstellen), um vereinzelt auftretende Löcher mit einem Durchmesser von etwa 1 nm und in seltenen Fällen um ein ungeordnetes Kohlenstoffgitter ,…”
Section: Methodsunclassified
“…The performance of the as‐prepared graphene varies between 100 and 1000 mAh g −1 when used as electrodes for LIBs, depending especially on the structural design, electrode processing, mass loading, and the way to assemble graphene sheets. Seiler et al found that only well‐ordered, highly crystalline graphite delaminates into oxo‐functionalized graphene, whereas other graphite grade reverts back to graphite during hydrolysis . The electronic oxidation significantly lowered the friction of sulfuric acid confined between layers, initiating the intercalation process.…”
Section: Preparation Of Carbon‐based Nanomaterialsmentioning
confidence: 99%